Betel Leaf Extract Efficacy on Wound Healing: A Systematic review - Darmawan, Awal; Yusuf, Saldy; Tahir, Takdir; Syahriyani, St (STRADA : Jurnal Ilmiah Kesehatan, 2021)
Betel leaf extract effectively accelerates wound healing. To identify the potency of betel leaf extract in the inflammatory phase, proliferation and remodeling of wound healing phases. Literature quest: PubMed, EBSCO host, Proquest, Science Direct, DOAJ and GARUDA. As many as five articles were reviewed, In acute wounds, the level of IL-1β betel leaf extract at a concentration of 3% (ρ˂ 0.002, r = 0.701) has an effect on inflammation. Diabetes mellitus ulcers, blood vessel growth and increased collagen layer thickening affect cell proliferation, increased epithelialization, more melanin, melanocyte and fibrous tissue formation (ρ<0.05), increased granulation tissue weight (ρ<0.05), hydroxyproline content increased (ρ<0.05), epidermal thickening, more lots of fibroblasts and few macrophages, and inhibiting bacterial growth (ρ<0.05). Betel leaf extract has the potential to heal wounds both acute wounds, infection wounds and diabetic ulcers.